Improving Flood Hazards Assessment with Geospatial and Geophysical Integration: A Case Study of Lokoja, Nigeria - Mogaji, Kehinde Anthony; Komolafe, Akinola Adesuji; Akinlalu, Ayokunle Adewale; Adeyemi, Adedoyin Benson; Adeniyi, Oluwafemi Tolulope; Dada, Boluwatife Mosebolatan (Journal of Science, Technology and Innovation Research, 2026)
Flooding is a persistent problem in Lokoja, located at the confluence of the Niger and Benue rivers. This study integrated geospatial and geophysical data to map flood susceptibility in the Sub-Niger River Basin. Using remote sensing, GIS, and aeromagnetic data, seven factors—elevation, slope, drainage density, distance from rivers, lineament density, land use/land cover, and precipitation—were analyzed with the Analytical Hierarchy Process. Results show 36.85% of the basin is highly flood-prone, especially around Ganaja and Gadumo. Model validation (AUC = 0.81) confirms strong accuracy. The map supports floodplain zoning, land-use planning, and improved flood risk management in Lokoja.